EPISTEMOLOGICAL OUTLOOK OF ZAINI DAHLAN’S TAFSIR AL-QUR’AN JUZ 30 - Najma, Dzatan; Iwanebel, Fejrian Yazdajird (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
The development of modern Qur’anic interpretation in Indonesia has been characterized by the emergence of thematic exegesis. In this case, chapter 30 of the Qur’an has drawn much attention, among them is Tafsir Al-Qur’an Juz 30 written by Zaini Dahlan. This work is quite interesting as it is written by an academic Muslim scholar, pedagogical in nature, and having attention much on poetical language of the Qur’an. By using the epistemological framework and theories of Qur’anic interpretation, this article aims to find the source, method, style, validity, and orientation of Zaini Dahlan’s interpretation. The article, then, argues that one of Zaini Dahlan’s contributions to the discourse of Indonesian Qur’anic studies lies on his attention to the poetic structure of the Qur’an which directed to strengthen theological and pedagogical aspects. In his epistemological structure, Dahlan uses various sources of knowledge most notably from the Qur’an, hadith, history, and scholars’ interpretation, which are generally coupled with the dominance of reason (bi al-ra’y) over narrations (bi al-ma’thur). In addition, Dahlan also applied the thematic method of surahs which is framed by the poetic nuances of the Qur’an. As for the measure of truth, Dahlan seems to apply three theories of validity, namely coherence, correspondence, and pragmatics.